Direct Athlete Support (DAS) scheme (2012)
The Australian Government Direct Athlete Support (DAS) scheme, administered by the Australian Sports Commission, provides direct financial assistance to our world-class athletes in sports where Australia has a successful track record. In 2011-12, the DAS scheme is allocating $8.43 million to support approximately 680 of Australia`s top athletes in 33 sports, assisting with their preparations for the London 2012 Olympic and Paralympic Games, and beyond.